A Critical Review on Interest Rate as a Tool of Monetary Policy - diyah putriani; pras towo (Institute for Research and Community Empowerment (LPPM TAZKIA), 2015)
Objectives: This research is aimed to critically review the relationship between interest rate and economic downturnMethods: Meta-analysis.Results: The existing monetary policy will always create higher inflation rate overtime triggering economic crisis in the long run. This is not merely about how the monetary authority strictly manages the supply and demand for money in the economy.Conclusion:This paper concludes that interest rate give negative contribution to the economic growth.